Circular RNA SPI1 expression before and after induction therapy and its correlation with clinical features, treatment response, and survival of acute myeloid leukemia patients. Issue 3 (16th January 2023) - Xiong, Ting; Xia, Liqun; Song, Qiaoqiao
Abstract: Background: Circular RNA spi‐1 proto‐oncogene (circ‐SPI1) regulates cell proliferation, apoptosis, and bone marrow differentiation in acute myeloid leukemia (AML). This study aimed to assess the relationship of circ‐SPI1 expression with the clinical features, induction therapy response, and survival of AML patients. Methods: In total, 80 AML patients were included with bone marrow (BM) samples collected at baseline and after induction therapy. Additionally, 20 healthy donors (HDs) and 20 disease controls (DCs) were enrolled with BM samples collected after enrollment. BM circ‐SPI1 expression was detected by reverse‐transcription quantitative polymerase chain reaction assay. Results: Circ‐SPI1 expression was highest in AML patients, moderate in DCs, and lowest in HDs (median (interquartile range): 3.01 [2.02–4.14] versus 1.71 [1.01–2.85] versus 0.98 [0.74–1.71]) ( p < 0.001). Moreover, lower circ‐SPI1 expression was related to its decreased located gene SPI1 expression ( p = 0.029), white blood cells (WBC) < 18.8 × 10 9 /L ( p = 0.010), trisomy 8 ( p = 0.025), and more favorable risk stratification ( p = 0.014) in AML patients. Additionally, circ‐SPI1 expression was reduced in AML patients after induction therapy ( p < 0.001), and its low expression after induction therapy was correlated with the achievement of complete remission ( p < 0.001). Furthermore, circ‐SPI1 decline ≥30% during therapy (versus <30%) was independently related to longer event‐free survival (EFS) (hazard ratio (HR): 0.445, p = 0.028) and overall survival (OS) (HR: 0.319, p = 0.025) in AML patients. Conclusion: Decreased circ‐SPI1 expression is related to lower WBC, favorable risk stratification, and better therapy response; moreover, its decline during therapy is an independent factor to predict longer EFS and OS in AML patients. Abstract : This study aimed to assess the relationship of circular RNA spi‐1 proto‐oncogene (circ‐SPI1) with the clinical features, induction therapy response, and survival of acute myeloid leukemia (AML) patients. Bone marrow circ‐SPI1 was detected by reverse‐transcription quantitative polymerase chain reaction assay in 80 AML patients at baseline and after therapy, and 20 healthy donors (HDs), and 20 disease controls (DCs) after enrollment. Circ‐SPI1 was highest in AML patients, moderate in DCs, and lowest in HDs. In AML patients, lower circ‐SPI1 was related to decreased SPI1, white blood cells (WBC) < 18.8 × 10 9 /L, trisomy 8, and favorable risk stratification. Circ‐SPI1 after therapy was reduced, and its low expression was correlated with complete remission. Furthermore, circ‐SPI1 decline ≥30% during therapy independently predicted longer event‐free survival (EFS) and overall survival (OS). Overall, decreased circ‐SPI1 is linked with lower WBC, favorable risk stratification, and better therapy response, whose decline independently predicts longer EFS and OS in AML patients.